Desain Modul Ajar Berbasis Critical Thinking dan Creativity pada Materi Kesebangunan - Putri, Melita Yofanka Winanto; Pramesti, Cicik; Suryanti (Polinomial : Jurnal Pendidikan Matematika, 2025)
The ability to think critically and creatively is an important 21st century skill to be developed in learning, including in the curriculum in junior high school. However, international studies such as PISA show that this ability is still low among Indonesian students. This is exacerbated by the dominance of conventional learning methods and teaching methods that do not support the development of high-level thinking skills. This research aims to develop a teaching module based on critical thinking and creativity in regenerative materials for junior high school students. The method used is Research and Development (R&D) with the ADDIE (Analyse, Design, Development, Implementation, Evaluation) model. The subject of the study was a 7H student of SMP Negeri 1 Nglegok. The data were analyzed descriptively through the results of interviews and questionnaires. The results of the interviews were used to describe the responses of teachers and students to the module, while the questionnaire data was analyzed with a percentage technique to assess the feasibility level of the module. As a result, teachers gave a score of 93 and positive responses to the module. The average student score was 79%, with the majority rating the modules "Good" and "Excellent". Interviews show that students are more enthusiastic about learning. Thus, this module is suitable to be used to support the development of students' critical and creative thinking skills.